A Modified Trap for Adult Sampling of Medically Important Flies (Insecta: Diptera) - Kamran Akbarzadeh; Javad Rafinejad; Jamasb Nozari; Yavar Rassi; MohammadMehdi Sedaghat; Mostafa Hosseini (Tehran University of Medical Sciences, 2015)
Background: Bait-trapping appears to be a generally useful method of studying fly populations. The aim of this study was to construct a new adult flytrap by some modifications in former versions and to evaluate its applicability in a subtropical zone in southern Iran. Methods: The traps were constructed with modification by adding some equipment to a polyethylene container (18×20× 33 cm) with lid. The fresh sheep meat was used as bait. Totally 27 adult modified traps were made and tested for their efficacies to attract adult flies. The experiment was carried out in a range of different topographic areas of Fars Province during June 2010. Results: The  traps were  able  to  attract  various groups of  adult flies  belonging to  families of:  Calliphoridae, Sarcophagidae, Muscidae, and Faniidae. The species of Calliphora vicina (Diptera: Calliphoridae), Sarcophaga argyrostoma (Diptera: Sarcophagidae) and Musca domestica (Diptera: Muscidae) include the majority of the flies collected by this sheep-meat baited trap. Conclusion: This adult flytrap can be recommended for routine field sampling to study diversity and population dy- namics of flies where conducting of daily collection is difficult.